Developing reading comprehension through digital storytelling / Rofiza Aboo Bakar and Nur Farah Nizza Jaafar - Aboo Bakar, Rofiza; Jaafar, Nur Farah Nizza (Universiti Teknologi MARA, Pahang, 2017)
Although Azzam was nineteen years old and a diploma student in a university, he found that comprehending expository texts in English was an obstacle. However, when offered the chance to create a digital story, Azzam became deeply engaged and he began reading more texts. He was able to create a digital story that required him to activate his background knowledge, search for additional reading materials, consider alternative interpretations, and become philosophical. In the paper, it is argued that digital storytelling is a means for Azzam to respond well to expository texts by using the cognitive, metacognitive and affective reading elements. Rosenblatt's reader-response theory (1978) was embraced as the theoretical framework. Digital storytelling is believed to have the potential to play a significant role in helping students comprehend expository texts effectively.